Contract linkages and resource use in grain production: The Argentine pradera pampeana - Marcos Gallacher (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2012)
This paper analyzes contractual arrangements in barley production in the Argentine pradera pampeana region. Barley constitutes an interesting case-study: its production and marketing conditions result in some degree of vertical contracting between primary producers and processors. Vertical coordination via contracting, however, is considerably less than that observed for example in poultry or some types of vegetable and fruit production. Barley is thus an intermediate case between coordination via impersonal market transactions and that resulting from different degrees of vertical integration. The objective of the paper is to determine the impacts of contracting on decisions such as input purchasing agreements, output marketing sharing, vertical integration, risk management and the use of technical know-how. The impact of contracting arrangements on input use and technology choice is also explored. Findings include the following. First, input purchase sharing, or output marketing sharing arrangements are infrequent amongst farmers. Some evidence exists, however, of barley farmers engaging in these arrangements more than farmers producing alternative crops. The (partial) asset-specific nature of the barley crop may explain these differences. Second, a higher proportion of barley farmers engage in different types of vertical arrangements with input suppliers or output purchasers. Third, farmers participating in the barley vertical chain are more likely to use formal insurance instruments than farmers producing other crops. Fourth, significant differences exist in input (fertilizer and ag chemical), and technical-know how between farmers that participate and those that do not participate in vertical arrangements with input suppliers and output purchasers. Formal contracting appears, in general, to have a positive impact on all these dimensions. The paper shows that contracts between barley producers and processors are relatively simple, relying for compliance on reputation and good-will more than on the formal written word. Possibly, relatively low benefits from non-compliance result in this type of arrangement working well. The paper also shows, however, that private arbitration, mediation and quality inspection institutions exist in order to reduce both the probability and costs of litigation. The Camara Arbitral (in existence since 1905) is an interesting example of this type of institution.
Keywords: 330